UMS-ALIEN: UMS active learning in engineering education - Mohd Kamaruddin Abd Hamid (Penerbit UTM Press, 2024)
The Universiti Malaysia Sabah Active Learning in Engineering Education (UMS-ALIEN) initiative, part of the UMS Future Ready Engineering Educators (UMS-Future) framework, introduces a structured, hierarchical approach to engineering education. The framework consists of ten progressive competency levels, starting with foundational active learning techniques and advancing to blended cooperative problem-solving methodologies. UMS-ALIEN integrates strategies such as cooperative learning, problem-based learning, and blended learning, supported by tools like Learning Management Systems (e.g., Moodle) and discipline-specific simulators (e.g., Aspen HYSYS). The initiative transitions educators from traditional roles to facilitators, fostering participatory learning environments that prepare students for real-world challenges. Implemented across multiple engineering courses, UMS-ALIEN demonstrates improvements in student performance and skill acquisition, earning international recognition for its innovative contributions to active and blended learning in engineering education.